2014
DOI: 10.1371/journal.pone.0088657
|View full text |Cite
|
Sign up to set email alerts
|

How River Rocks Round: Resolving the Shape-Size Paradox

Abstract: River-bed sediments display two universal downstream trends: fining, in which particle size decreases; and rounding, where pebble shapes evolve toward ellipsoids. Rounding is known to result from transport-induced abrasion; however many researchers argue that the contribution of abrasion to downstream fining is negligible. This presents a paradox: downstream shape change indicates substantial abrasion, while size change apparently rules it out. Here we use laboratory experiments and numerical modeling to show … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 135 publications
(140 citation statements)
references
References 38 publications
7
131
0
2
Order By: Relevance
“…However, little information about the particle shape variation in slope erosion processes is found. Domokos et al (2014) indicated that river-bed sediments displayed two universal downstream trends: fining, in which particle size decreased; and rounding, where pebble shapes evolved toward ellipsoids. Rounding is known to result from transport-induced abrasion.…”
Section: Particle Size Variation Of Smaller Abraded Aggregates (0038mentioning
confidence: 99%
“…However, little information about the particle shape variation in slope erosion processes is found. Domokos et al (2014) indicated that river-bed sediments displayed two universal downstream trends: fining, in which particle size decreased; and rounding, where pebble shapes evolved toward ellipsoids. Rounding is known to result from transport-induced abrasion.…”
Section: Particle Size Variation Of Smaller Abraded Aggregates (0038mentioning
confidence: 99%
“…In [5] it is shown that the evolution of S and U under the partial differential equations governing collisional abrasion processes can be modeled by letting S and U be random variables whose expected values decrease with time. While this trend has been verified both in laboratory experiments [6] and in the field [19], almost no pebbles in the primary classes {1, i}, {j, 1}, (i, j = 1, 2, . .…”
mentioning
confidence: 68%
“…Settinġ x =ẏ = 0 in (5), and noting that y = (x 2 − µ 1 )/(2αx + µ 2 ) from the first equation, we may eliminate y from the second equation to obtain the fixed point condition (6) F µ1,µ2,α (x) = a 4 x 4 + a 3 x 3 + a 2 x 2 + a 1 x + a 0 = 0, where…”
Section: Dynamical Partmentioning
confidence: 99%
“…Debido a que ambos ambientes presentan cinemáticas, dinámicas físicas y fuerzas disímiles, generan formas peculiares de guijarros, lo que permite distinguir su origen geológico según algunos de sus atributos morfológicos (Dobkins y Folk 1970;Kelly 1983). En los sistemas fluviales el desplazamiento del sedimento ocurre en un eje lineal y en un solo sentido, variando la intensidad y fuerza del transporte según la pendiente y alimentación del afluente, donde el ruedo por arrastre crea guijarros en general de formas esferoidales u ovoidales en el cual la abrasión se aplica similarmente en todas las superficies de la roca (Domokos et al 2014;Kelly 1983). En estos casos el grado de redondeamiento del guijarro dependerá de su ubicación en el eje de descenso del curso fluvial, presentando mayor grado de pulimento hacia su sección final debido a una historia más larga de abrasión (Attal y Lavé 2009).…”
Section: Detail Of Some Of the Decorated Hammerstones From Taller B unclassified